PENGGUNAAN MEDIA PENGEMBANGAN BAHAN AJAR FLIP BOOK PADA MATERI SPREADSHEET KELAS X SMK - Erika Dewi Nur Ngaini; Setyo Irman Fa'urachmad; Luqman Hakim; Amirul Arif; ALFINA FIRDA SAKTI (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2025)
This research is expected to produce the development of spreadsheet learning media using Flip Book and steps in excel learning for grade X SMK students. Education is very important for the progress of a nation with the main goal of developing the potential of students to become individuals who are faithful, have noble character, and competent. In the context of national education, improving the quality of learning is a priority, especially through innovation in teaching methods and media. The purpose of this study is to develop a Flip Book application that functions as an educational medium in the topic of Spreadsheet, which is expected to increase student attention and understanding. The research method used is Research and Development (R&D) which includes needs analysis, product design, development, testing, and implementation. The research findings show that the use of Flip Book can create an interesting and interactive learning environment while increasing student participation in the learning process. Thus, the development of technology-based teaching materials such as Flip Book is expected to support the effectiveness of learning and improve student learning outcomes in computer-related disciplines. This study concludes that innovation in learning media, a good learning environment will greatly affect the success of learning. Therefore, we need to create a learning atmosphere that makes students feel at home and inspired. and encourage students to be directly involved in the education process.